Glaucoma Burden in a Public Sector Hospital - M. Aamir Shahzad, P.S. Mahar (Pakistan Journal of Ophthalmology, 2008)
Purpose: To determine the demographic pattern and type of glaucoma presenting to our hospital and the modalities of medical and operative treatment performed Materials and Methods: Case records of all patients registered at glaucoma clinic from 1st May 2002 to 30th April 2003 were reviewed. Data was collected on a form and entered in SPSS. Multiple variables were collected and analyzed. Results: A total of 80,767 patients were seen in the hospital with different eye problems. The number of patients referred to the glaucoma division was analyzed and 447 patients were confirmed with the diagnosis of glaucoma (0.55%). Their demography showed 287 (64.2%) patients were male and 160(35.8%) were female. Age distribution showed 383 (85.7%) patients were 40 years or older. Primary glaucoma was seen in 345 (77.2%) patients, out of which 186 (41.6%) had primary open angle glaucoma (POAG) and 137 (30.67%) had chronic angle closure glaucoma (CACG). Secondary glaucomas were seen in 102 (22.8%) patients. Conclusion: Primary open angle glaucoma was still the most prevalent type of glaucoma seen in our clinic but chronic angle closure glaucoma also involved a significant number of patients. Most patients presented very late when their central vision was compromised or their glaucoma was detected at an early stage due to eye examination carried out due to some other ocular complaint. Intensive medical and surgical treatment was shown to control the disease in most of the patients.